Posterior basolateral amygdala to ventral hippocampal CA1 drives approach behaviour to exert an anxiolytic effect - Pi, Guilin; Gao, Di; Wu, Dongqin; Wang, Yali; Lei, Huiyang; Zeng, Wenbo; Gao, Yang; Yu, Huiling; Xiong, Rui; Jiang, Tao; Li, Shihong; Wang, Xin; et al. (Nature communications, 2020)
The basolateral amygdala (BLA) and ventral hippocampal CA1 (vCA1) are cellularly and functionally diverse along their anterior–posterior and superficial-deep axes. Here, we find that anterior BLA (aBLA) and posterior BLA (pBLA) innervate deep-layer calbindin1-negative (Calb1−) and superficial-layer calbindin1-positive neurons (Calb1+) in vCA1, respectively. Photostimulation of pBLA–vCA1 inputs has an anxiolytic effect in mice, promoting approach behaviours during conflict exploratory tasks. By contrast, stimulating aBLA–vCA1 inputs induces anxiety-like behaviour resulting in fewer approaches. During conflict stages of the elevated plus maze task vCA1 Calb1+ neurons are preferentially activated at the open-to-closed arm transition, and photostimulation of vCA1 Calb1+ neurons at decision-making zones promotes approach with fewer retreats. In the APP/PS1 mouse model of Alzheimer’s disease, which shows anxiety-like behaviour, photostimulating the pBLA–vCA1 Calb1+ circuit ameliorates the anxiety in a Calb1-dependent manner. These findings suggest the pBLA–vCA1 Calb1+ circuit from heterogeneous BLA–vCA1 connections drives approach behaviour to reduce anxiety-like behaviour. Projections from the anterior and posterior basolateral amygdala (pBLA) to the ventral hippocampus CA1 (vCA1) are heterogenous. Here the authors show that activating the pathway from pBLA to vCA1 calbindin 1 positive neurons has an anxiolytic effect in approach-avoidance tasks in mice.